The evaluation of food allergy knowledge and attitude in different food sectors and the effectiveness of video-based training - Aytulu, Tugce; Gundogdu, Beliz Su; Yayci, Elif; Ezelsoy, Isil; Buyuktiryaki, Betul; Veznikli, Mert; Isik, Sacide Rana; Sackesen, Cansin (Frontiers in Nutrition, 2025)
ObjectiveFood allergies are common in the food industry. The knowledge and attitude of catering staff are crucial in preventing food allergy (FA)-related reactions. The study aimed to determine the knowledge of FA and evaluate the effectiveness of video-based allergy training for catering personnel in three sectors: restaurants, schools, and hospitals.MethodsResearch has been conducted on workers in three different catering industries: (i) restaurant chains, (ii) school kitchens, and (iii) hospital kitchens. The study involved administering surveys to the staff to measure their demographic data (11 questions), attitude (12 questions), and knowledge level (24 questions) about FA. After taking the pre-test, the participants who watched a 32-min video on FA were asked to fill out post-test questionnaires measuring their knowledge and attitudes.ResultsAt the beginning, 619 participants took the pre-test. 45.7 and 40.9% (n = 253) had a previous food Safety Certificate and food allergy training, respectively. Sixty-four percent (n = 397) received our video-based FA training. Among the participants who completed video-based training and the post-test, some knowledge and attitude items improved, but some did not, compared to the pre-test results. Knowledge levels were similar between the previously FA-trained and those untrained individuals.ConclusionOur results show that the participants’ baseline level of knowledge and attitude for FA needs improvement. After the video training, the level of improvement in some items of knowledge and attitude was significant, but it was lower than expected. It is essential for training to not only provide accurate information but also aim to correct any known misconceptions.